Opting Out of The Maxim in Kung fu Panda 2 Movie: Pragmatics Study - Amelia, Putri Mega; Hendar, Hendar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to identify the types of opting out of maxim strategies and to analyze the reason of conflict found in the Kung Fu Panda 2 movie. This research uses descriptive qualitative method as the purpose of making this research is to analyze the type of opting out strategies and the reason of conflict the use of opting out strategies. The main theory used to identify opting out strategies is taken from Grice (1975) and Perrine (1984:56) in Amanda, A (2017) dealing with reason of conflict. The results type of opting out of the research showed that there were 23 data obtained which respectively consisted of 5 data (22%) on opting out of maxim quantity, 6 data (26%) on opting out of maxim quality, 7 data (31%) on opting out of maxim manner, and 5 data (21,7%) on opting out of maxim relation. Meanwhile, the reason of conflict that influenced the use of opting out strategies consisted of 15 data (65,2%) on internal conflict, 8 data (34,7%) on external conflict. Based on the data obtained above, it could be clearly seen that the most common type of opting out strategies found in Kung Fu Panda 2 movie was opting out of quality (31%) and the most common type of conflict found in the use of opting out strategies was internal conflict (65,2%). Keywords: Conflict, Maxim, Opting Out, Pragmatics Study